PEMANFAATAN KEARIFAN LOKAL DALAM PEMBUATAN KERIPIK COMBRO SEBAGAI MEDIA PENGENALAN BUDAYA PADA ANAK USIA DINI - Dita Nurul Istiqomah; Istiqomah Istiqomah; Ahmad Khoiri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Local wisdom is a cultural asset that reflects the identity and noble values ​​of a society. In Indonesia, the diversity of local cultures is one of the riches that need to be preserved, especially amidst the rapid flow of globalization that brings changes to the lifestyle and values ​​of the younger generation. This study aims to examine how the use of local wisdom in making combro chips can be an effective educational medium to introduce local culture to early childhood. This study uses a descriptive qualitative approach to describe how the use of local wisdom in making combro chips can be used as a medium for introducing culture to early childhood. The results of the study indicate that the activity of making combro chips can be an effective medium to introduce local culture to early childhood.